2022
DOI: 10.53974/unza.jonas.5.1.710
|View full text |Cite
|
Sign up to set email alerts
|

Machine Accidents and Project Delivery in Kwazulu-Natal Construction Industry

Abstract: This article identified machine accidents, the number of days lost, cost impact and related accidents in the Construction Industry in the KwaZulu-Natal province of South Africa. Accidents in the construction industry cause severe challenges to the business. The critical parameters for assessing project deliveries are health and safety, cost, time and project quality. The events of accidents on construction premises sabotages these critical parameters of delivery. The main focus of this article was to determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…These 148 questionnaires represented 87.06% response rate. This response rate is higher than 25.4% (Emuze, 2011) 33.5% (Olatunji, 2010) in the construction industry. The questionnaire consisted of two sections.…”
Section: Methodsmentioning
confidence: 60%
See 1 more Smart Citation
“…These 148 questionnaires represented 87.06% response rate. This response rate is higher than 25.4% (Emuze, 2011) 33.5% (Olatunji, 2010) in the construction industry. The questionnaire consisted of two sections.…”
Section: Methodsmentioning
confidence: 60%
“…The Cronbach's alpha reliability of challenges associated with contractor selection strategy is 0.87. The measured Cronbach's α recorded for this study revealed that the reliability of the questionnaires' constructs is high according to (Olatunji, 2010); all exceeding the cut off score of 0.7. This indicated that the questionnaire constructs are highly reliable (consistent) free from rom error.…”
Section: Methodsmentioning
confidence: 66%
“…This marvel is additionally likewise seen in Ghana where Windapo (2013) sees that reviews uncover expansion in cost overwhelms, deferred fruition, inadmissible and neglected undertaking goals in most development projects. While exploring the subject of task delays in South Africa, Olatunji (2010) sees that it is a marvel that can be ascribed to the powerlessness of the customer/his delegate and the venture group to have an exhaustive perspective on the development project from beginning to consummation. Musa et al, (2011) express that development delay has gotten endemic in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…Umeokafor et al (2022) pointed out that the accident rate within African countries is 21.1 fatalities per every 100,000 workers. In South Africa, for example, there is a positive relationship between lost days and the average cost per accident, which means that for every increase in lost days, there is a corresponding increase in the cost of accidents (CoA) (Aiyetan & Anugwo, 2021). According to Bavafa et al (2018), the case in Ghana is a concern.…”
Section: Introductionmentioning
confidence: 99%